2019
DOI: 10.3171/2017.10.jns17359
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of central nervous system infectious diseases: a meta-analysis and systematic review with implications for neurosurgeons worldwide

Abstract: OBJECTIVE Central nervous system (CNS) infections cause significant morbidity and mortality and often require neurosurgical intervention for proper diagnosis and treatment. However, neither the international burden of CNS infection, nor the current capacity of the neurosurgical workforce to treat these diseases is well characterized. The objective of this study was to elucidate the global incidence of surgically relevant CNS infection, highlighting geographic areas for targeted improvement in neurosurgical cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 161 publications
3
81
0
Order By: Relevance
“…8,23 The global volume of pediatric brain tumors, cerebrovascular anomalies, and se- vere central nervous system infections add to the overall burden of pediatric neurosurgical disease. 8,20 For comparison, in 2016 there were an estimated 160,000 new cases of HIV 14 and 1 million new cases of tuberculosis diagnosed in children. 25 In developing countries, little attention is given to pediatric surgical disease.…”
Section: Discussionmentioning
confidence: 99%
“…8,23 The global volume of pediatric brain tumors, cerebrovascular anomalies, and se- vere central nervous system infections add to the overall burden of pediatric neurosurgical disease. 8,20 For comparison, in 2016 there were an estimated 160,000 new cases of HIV 14 and 1 million new cases of tuberculosis diagnosed in children. 25 In developing countries, little attention is given to pediatric surgical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the advent of CT imaging reduces mortality in the setting of trauma and infections, which are more frequent in lower-income settings. 9,12,14,23 Lack of timely imaging leads to delay in surgical management and poor patient outcomes. 18,23 Creating awareness of such need and involving all stakeholders, including the local governments, is essential to ensure sustainability and durability of instrument provision.…”
Section: Resource Availabilitymentioning
confidence: 99%
“…6 They calculated an operative deficit of 5 million neurosurgical cases per annum, with traumatic brain injury, stroke-related conditions, tumors, hydrocephalus, and epilepsy comprising the majority of the global neurosurgical disease burden. 4,5,[7][8][9][10]14,15,18 They further estimated that 23,300 additional neurosurgeons are needed to address the deficit, mostly in Africa and Southeast Asia.…”
Section: Current Capacity and Deficit In Essential Neurosurgical Carementioning
confidence: 99%